DOI: 10.33915/etd.4340
|View full text |Cite
|
Sign up to set email alerts
|

Age and growth of Appalachian brook trout in relation to life-history and habitat features

Abstract: Age and growth of Appalachian brook trout in relation to life-history and habitat features Jason Thomas Stolarski Currently, it is perceived that brook trout (Salvelinus fontinalis) are experiencing reductions in both range and abundance across their east coast distribution. Data identifying key habitat features influencing growth rates of these fish will be valuable to managers conducting remediation efforts as growth at age has important consequences to survival and fecundity. Of particular importance within… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 73 publications
(137 reference statements)
0
5
0
Order By: Relevance
“…Sample sections were bounded at both upstream and downstream ends with block nets to meet the assumption of a closed population. Fish sampling at tributary sites was conducted as part of a concurrent study, thus requiring sampling procedures in excess of what would be required to obtain a representative sample of individuals from the population (Stolarski 2007). Summer sampling was chosen because of reduced brook trout growth rates and the high likelihood that fluvial and resident individuals were spatially segregated at this time (Power 1980; Petty et al.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sample sections were bounded at both upstream and downstream ends with block nets to meet the assumption of a closed population. Fish sampling at tributary sites was conducted as part of a concurrent study, thus requiring sampling procedures in excess of what would be required to obtain a representative sample of individuals from the population (Stolarski 2007). Summer sampling was chosen because of reduced brook trout growth rates and the high likelihood that fluvial and resident individuals were spatially segregated at this time (Power 1980; Petty et al.…”
Section: Methodsmentioning
confidence: 99%
“…Brook trout was sampled during 3 weeks in July of 2006 from three representative 100-m sections (up, mid (Stolarski 2007). Summer sampling was chosen because of reduced brook trout growth rates and the high likelihood that fluvial and resident individuals were spatially segregated at this time (Power 1980;Petty et al 2005;Utz & Hartman 2006).…”
Section: Fish Samplingmentioning
confidence: 99%
“…Simply having large amounts of woody materials in a stream will not maximize Brook Trout population stability and resilience if the habitat itself is not stable. Previous studies by (Sweka and Hartman 2006, Stolarski 2007, Sweka et al 2010, Studinski et al 2017 have shown that adding large wood to streams haphazardly does little to increase pool habitat or stability. In those studies, adding large wood resulted in new pool formation with low stability, and at the expense of other pools.…”
Section: Discussionmentioning
confidence: 96%
“…These categorizations were validated using scale-aging techniques (Devries and Frie 1996, Stolarski 2007…”
Section: Data Collectionmentioning
confidence: 99%
“…Macroinvertebrate metrics such as richness, percentage of Ephemeroptera, Plecoptera, and Trichoptera (EPT), and West Virginia Stream Condition Index (WVSCI) were compared between a set of previous samples in these streams from a spring 2007 study (Stolarski 2007)…”
Section: Study Sites and Field Samplingmentioning
confidence: 99%